Thyroid dysfunction and its association with microvascular complications in patients with type 2 diabetes mellitus in south India. Issue 4 (July 2020) - Reddy, Nishitha; Pradeep, T.V.S.; Tirupati, Sunanda; Sarathi, Vijaya; Kumar, Dileep
Abstract: Background and aims: To study the prevalence of thyroid disorders and their association with microvascular complications among adult type 2 diabetes mellitus (T2DM) patients from south-coastal Andhra Pradesh, India Methods: This cross-sectional study included 500 subjects with T2DM and was conducted in a tertiary health care center from south-coastal Andhra Pradesh. Participants previously diagnosed with thyroid disorders were excluded from the study. Results: Thyroid dysfunction was observed in 98 (19.6%) subjects of which subclinical hypothyroidism (n = 66, 13.2%) was the most common. Subclinical hypothyroidism (SCH) was more frequent in obese patients (16.2% vs 7.6%, p = 0.007) and metformin users (9.6% vs 18.7%, p = 0.0044). Diabetic retinopathy (27.3% vs 8.9%, p = 0.001) was significantly more frequent in SCH patients than euthyroid T2DM patients. Conclusion: Among T2DM patients from south-coastal Andhra Pradesh the prevalence of thyroid dysfunction, especially that of SCH was high; SCH was more frequent among obese and nonmetformin users and was associated was associated with increased risk of diabetic retinopathy. Highlights: Prevalence of thyroid dysfunction was high in South Indian adults with type 2 diabetes mellitus. Subclinical hypothyroidism was associated with more frequent occurrence of diabetic retinopathy.